Unexpected Methane Emissions From Old Small Fishing Vessels in China - Wang, Lizhi; Du, Wei; Shen, Huizhong; Chen, Yuanchen; Zhu, Xi; Yun, Xiao; Shen, Guofeng; Chen, Yilin; Liu, Junfeng; Wang, Xuejun; Tao, Shu (Frontiers in Environmental Science, 2022)
Diesel-fueled ships have long been considered to contribute a marginal fraction of the global methane (CH4) emission budget compared to liquified natural gas (LNG)-fueled ships. Here, based on real-world measurements, we find that a specific yet-overlooked group of diesel-fueled ships–the old small fishing vessels (OSFVs)–is associated with high levels of CH4 emissions. The emission factors of CH4 from OSFVs is on average 5.2 ± 6.4 g CH4 per 1 kg fuel consumed, approaching EFCH4 of LNG-fueled ships (5.3–30.1 g/kg) and being at least six times EFCH4 of other types of diesel-fueled ships (0.0–0.9 g/kg). We estimate that CH4 emissions from OSFVs in China amount to 570–2,240 t per year, which is comparable to the total CH4 emission from all LNG-fueled ships worldwide. Our results thus call for revision of the global CH4 emission inventory for shipping.